Demonstration of a free-space optical communication system using a solar-pumped laser as signal transmitter. (30th March 2017) - Guan, Z; Zhao, C M; Yang, S H; Wang, Y; Ke, J Y; Zhang, H Y
Abstract: A free-space optical communication system with a sun light directly pumped laser as the signal transmitter was demonstrated. A 0.6 × 0.6 m Fresnel lens was used as the primary concentrator to collect the solar light. 6.8 W continuous wave laser power was obtained from a 4 mm diameter grooved Nd:YAG rod. The output intensity was modulated with a video signal via a LiNbO3 Mach–Zehnder optoelectronic modulator. The video signal with a resolution of 1920 * 1080/frame and the frame rate of 25 Hz was transmitted over five-meter free-space in real time with high fidelity. The transmission rate was 125 Mbps and bit error rate was lower than 10 −6 . This research shows the feasibility of applying a solar light directly pumped laser for free-space optical communication, which is significant for telecommunications between satellites.